NEW DATA ON THE LATE QUATERNARY STRATIGRAPHY AND PALEOGEOGRAPHY OF THE WIJDEFJORDEN REGION (WEST SPITSBERGEN) - Sharin V.V.; Alekseev V.V.; Dymov V.A.; Pogodina I.A.; Bol'shiyanov D.Yu.; Gusev E.A. (My University, 2007)
The World Ocean region with Spitsbergen Archipelago is one of the most indicative areas in terms of paleogeography for assessing global climatic fluctuations in the late Quaternary and for their long-term prediction. We carried out geomorphological, lithological, and faunal studies on the Wijdefjorden eastern coast in the southern Ny Frisland Peninsula. A series of well-defined accumulative–abrasion marine terraces composed of sediments 2–5 m thick was revealed here within the Flatoyrdalen outwash valley springing from the Cookbreen outlet glacier. Proterozoic bedrocks or Late Pleistocene sedimentary rocks occur in the terrace socle.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная